A magia das cores e formas - Carvalho , Genilza Aparecida Gonçalves de; Alencar, Rosania Aparecida de Souza; Botassin, Rosa Maria Ferreira (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2023)
>>> ver pdf